EVALUASI KUALITAS PELLET PAKAN ITIK YANG DISUPLEMENTASI TEPUNG DAUN MENGKUDU (Morinda citrifolia) DAN DISIMPAN SELAMA 6 MINGGU (Quality evaluation of duct feed pellet supplemented with morinda (Morinda citrifolia) leave powder after 6 weeks storage) - Muhamad Rizqan Luthfi Akbar; Dwi Margi Suci; Indah Wijayanti (Buletin Ilmu Makanan Ternak, 2017)
ABSTRACT Ration in pellet form could increased feed efficiency level compared to mesh in poultry. The objective of the research was to  evaluate Morinda citrifolia leaves in ducks ration on the pellet physical quality and rancidity level after storing. The treatments diet contained 18 % of crude protein and 3000 kkal kg-1 metabolizable energy.  Pelleting diet process used simple wood pellet without steam, pellet knife and coller. The experiment was factorial using completely randomized design. Factor A was the percentage of mengkudu leaves (0, 2.5, 5 and 7.5%). Factor B was the period of storage (0, 3 and 6 weeks). The data were analyzed by using analysis of varian (ANOVA) and Duncan Multiple Range test. The variables were moisture content, water activity, density, compact bulk density, bulk density, pellet durability, pellet durability index, angle of repose, particle size, peroxide value, and fat content. The result showed that supplementation of Morinda citrifolia leaf and storage period significantly (P<0.05) affected the water activity and moisture content. Supplementation 7.5% of Morinda citrifolia leaves reduced (P<0.05) pellet density. The average pellet density in 0% Morinda citrifolia and 7.5% Morinda citrifolia were 1.27 g mL-1 and 1.22 g mL-1 respectively. Storing ducks pellet up to 6 weeks decreased physical pellet quality as indicated by increasing moisture content, water activity and the peroxide value. Keywords : Morinda citrifolia, pellet diet, peroxide value, storage